DESAIN DAN IMPLEMENTASI E-COMMERCE PADA INDUSTRI GERABAH ANTIK UD. KUNDI JAYA BLITAR - Khamim Mustofa; Mochammad Husni (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2024)
UD.KUNDI JAYA is one of the pottery industry in Indonesia, especially in Blitar. UD.KUNDI JAYA products include Vases, Pots, Set tables and chairs, kitchen utensils, ashtray and all kinds of other accessories are made of clay, which sold for cash (directly to the purchaser or consumer). UD.KUNDI JAYA in management is still using a simple way that every transaction is recorded and then archived in the book that have difficulties when analyzing transactions and determine the production and marketing strategies appropriately, addition of sales are still limited to only include Blitar and nearby towns. Thus the need for the transition from conventional systems that are still running into a computerized system so that the needs of the pottery industry in terms of data storage and marketing transactions more widely through the Internet (e-commerce) can be met, in addition to the existence of this system can be used as a means for consumers to obtain information about existing products in the company and everything related to the pottery industry UD.Kundi Jaya Blitar. To be competitive in the future where information technology has become an added value in the business world as well as provide a deeper ability to compete. So with this basic research tasks Special Programming with the title